2001
DOI: 10.1001/jama.286.7.807
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Soy-Based Formula in Infancy and Endocrinological and Reproductive Outcomes in Young Adulthood

Abstract: Exposure to soy formula does not appear to lead to different general health or reproductive outcomes than exposure to cow milk formula. Although the few positive findings should be explored in future studies, our findings are reassuring about the safety of infant soy formula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
218
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(229 citation statements)
references
References 44 publications
6
218
0
5
Order By: Relevance
“…These data suggest that soy formula may prolong the physiologic estrogenization of the newborn. Among the rare reports evaluating the long term reproductive health impact of soy formula, a retrospective cohort study found that women who participated in a soy formula study as infants reported no significant differences in the onset of puberty or in reproductive functions, but did report slightly longer menstrual bleedings and more discomfort than those who were fed with milk formulas (Strom et al, 2001). However, the true relevance of this study has been the subject of controversy, due to the lack of direct measurements of hormone levels and reproductive functions (Goldman et al, 2001;Tan et al, 2006).…”
Section: Soy-based Infant Formula: a Source For Concern?mentioning
confidence: 99%
“…These data suggest that soy formula may prolong the physiologic estrogenization of the newborn. Among the rare reports evaluating the long term reproductive health impact of soy formula, a retrospective cohort study found that women who participated in a soy formula study as infants reported no significant differences in the onset of puberty or in reproductive functions, but did report slightly longer menstrual bleedings and more discomfort than those who were fed with milk formulas (Strom et al, 2001). However, the true relevance of this study has been the subject of controversy, due to the lack of direct measurements of hormone levels and reproductive functions (Goldman et al, 2001;Tan et al, 2006).…”
Section: Soy-based Infant Formula: a Source For Concern?mentioning
confidence: 99%
“…However, at the present time, it is not known whether the high perinatal soy exposure among infant soy formula users has any effect on later breast cancer risk. The conclusions reached in reviews discussing the safety of infant soy formula suggest that it does not appear to cause adverse general health or reproductive outcomes or affect human growth (Strom et al, 2001). More cautious authors propose that the existing data are insufficient to draw definitive conclusions on safety and that the use of soy protein formulae should be limited only to those who cannot consume casein-based formulas (Turck, 2007).…”
Section: Ratsmentioning
confidence: 99%
“…Although it has been proposed (Irvine, 1995) that soybased infant formulas may impair the physical, physiological and behavioral development, a long-term follow-up study in men and women who had been fed soy formula during infancy (Strom et al, 2001) detected no adverse effects on more than 30 outcomes. In our study, the girls reported no health complications related to soy consumption.…”
Section: Soy Consumptionmentioning
confidence: 99%